Industrial China and its impact on Informality. - Fleary, Kevin Michael (International Journal of Management Excellence (ISSN: 2292-1648), 2017)
The informal economy has been the topic of debate for some time now and given its significant effect on the revenue, economists and policy decision makers alike have sought greater control to their dismay. This can be contributed to the lack of informal statistics on China, fueling assumptions that have not born results. To address the problem, this paper seeks to estimate the size of China’s informal economy using the Currency Demand Model. The central theme forwarded in this research is that China is experiencing its Lewis Turning Point and the industry changes positively impact the growth of the underground economy. Given this statement, the authors present a conceptual model that depicts the growth and movement of the informal economy in relation to China’s economic changes. As a means to provide intuition for decision makers as China transition to the 13th National Development Plan.